The Systems of Nonlinear Gradient Flows on Metric Spaces and Its Gamma-Convergence - Chang, Mao-Sheng; Lu, Bo-Cheng (Abstract and Applied Analysis, 2012)
We first establish the explicit structure of nonlinear gradient flow systems on metric spaces and then develop Gamma-convergence of the systems of nonlinear gradient flows, which is a scheme meant to ensure that if a family of energy functionals of several variables depending on a parameter Gamma-converges, then the solutions to the associated systems of gradient flows converge as well. This scheme is a nonlinear system edition of the notion initiated by Sylvia Serfaty in 2011.